Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Correction to: Reconstructed historical distribution and phylogeography unravels non-steppic origin of Caucasotachea vindobonensis (Gastropoda: Helicidae) - Łukasz Kajtoch; Angus Davison; Adele Grindon; Tamás Deli; Gábor Sramkó; Mariusz Gwardjan; Sergei Kramarenko; Dominika Mierzwa-Szymkowiak; Rafał Ruta; Radosław Ścibior; János Pál Tóth; Christopher M. Wade; et al. (Organisms Diversity & Evolution, 2018)

Reconstructed historical distribution and phylogeography unravels non-steppic origin of Caucasotachea vindobonensis (Gastropoda: Helicidae) - Łukasz Kajtoch; Angus Davison; Adele Grindon; Tamás Deli; Gábor Sramkó; Mariusz Gwardjan; Sergei Kramarenko; Dominika Mierzwa-Szymkowiak; Rafał Ruta; Radosław Ścibior; János Pál Tóth; Chris Wade; et al. (Organisms Diversity & Evolution, 2017)

RAD‐Seq derived markers flank the shell colour and banding loci of the Cepaea nemoralis supergene - Paul M. Richards; M. Maureen Liu; Natalie Lowe; John W. Davey; Mark L. Blaxter; Angus Davison (Molecular Ecology, 2013)
Studies on the classic shell colour and banding polymorphism of the land snail C epaea played a crucial role in establishing the importance of natural selection in maintaining morphological variation. Cepaea is also a pre‐eminent model for ecological genetics because the outward colour and banding phenotype is entirely genetically determined, primarily by a ‘supergene’ of at least five loci. Unfortunately, progress in understanding the evolution and maintenance of the C epaea polymorphism stalled, partly because of a lack of genetic markers. With a view to re‐establish C epaea as a prominent model of molecular ecology, we made six laboratory crosses of C epaea nemoralis , five of which segregated for shell ground colour ( C ) and the presence or absence of bands ( B ). First, scoring of colour and banding in 323 individuals found no recombination between the C and B loci of the supergene. Second, using restriction site–associated DNA sequencing ( RAD ‐ S eq) of two parents and 22 offspring, we identified 44 anonymous markers putatively linked to the colour ( C ) and banding ( B ) loci. The genotype of eleven of the most promising RAD ‐ S eq markers was independently validated in the same 22 offspring, then up to a further 146 offspring were genotyped. The closest RAD ‐ S eq markers scored are within ~0.6 centimorgan (cM) of the C ‐ B supergene linkage group, with the combined loci together forming a 35.8 cM linkage map of markers that flank both sides of the C epaea C ‐ B supergene.

Genetic signatures of population change in the British golden eagle (Aquila chrysaetos) - Brian P. Bourke; Alain C. Frantz; Christopher P. Lavers; Angus Davison; Deborah A. Dawson; Terry A. Burke (Conservation Genetics, 2010)

The recent history and population structure of five Mandarina snail species from subtropical Ogasawara (Bonin Islands, Japan) - ANGUS DAVISON; SATOSHI CHIBA (Molecular Ecology, 2006)
The effect of Pleistocene climate change on the organisms of tropical and subtropical regions is rather poorly understood. We therefore studied the land snail genus Mandarina (Bradybaenidae) of oceanic Ogasawara (Bonin Islands, Japan), with the aim of using population genetic data to understand their recent history. Our analysis of a mitochondrial 16S ribosomal RNA region from more than 600 snails in five ground‐living species suggests that populations on the small islands of Mukoujima, Anejima, Imotojima and Meijima, as well as on the low‐lying southern and central parts of Hahajima, have probably undergone recent bottlenecks followed by subsequent expansions. Except between the main island of Hahajima and Mukouijima, there is almost no evidence for gene flow among islands even though the islands were connected repeatedly by land bridges through the Pleistocene. Within islands the population structure is severe, suggestive of a long‐term, low level of gene flow ( F ST is frequently greater than 0.5 among geographically close populations). Finally, there is a marked genetic patchiness, meaning that genetically close populations are sometimes separated by genetically distant populations. These patterns could be a consequence of expansion from bottlenecks, low active dispersal and founder effects caused by rare long‐distance migrants. Unfortunately, the exact nature of the refugia and bottlenecks remains unknown because the palaeoclimate of this region is poorly understood. Dating the population size changes is also challenging because the molecular clock is uncertain. We suggest, however, that arid conditions or deforestation induced by decreased atmospheric CO 2 may have been the main factor in determining population size.

The evolution of extreme shell shape variation in the land snail Ainohelix editha : a phylogeny and hybrid zone analysis - Hiroaki Teshima; Angus Davison; Yasuhiro Kuwahara; Jun Yokoyama; Satoshi Chiba; Tatsuya Fukuda; Hideo Ogimura; Masakado Kawata (Molecular Ecology, 2003)
Ainohelix editha from Hokkaido, Japan, exhibit great geographical variation in their shell morphology. In particular, A. editha in two quite separate locations, Shimamaki and Samani, are striking because they are extremely flat and have a sharp keel, whereas at adjacent sites the shells are globular or depressed‐globular. We used mitochondrial 16S rRNA and nuclear ITS‐2 sequences to infer a phylogeny among 47 snails from 29 locations. Snails from the two keeled‐flat populations clustered separately in the phylogeny, suggesting that this unusual shell form could have evolved independently. A morphological analysis of shells collected along a transect between keeled‐flat and globular snail sites showed a cline for shell shape and the angle of the keel. Two different mtDNA lineages were found across the transect, with a cline for an ITS‐2 single nucleotide polymorphism. Together, the results may suggest a lack of reproductive isolation between keeled‐flat and globular snails, with possible introgression by hybridization.

Mitochondrial phylogeography and population history of pine martens Martes martes compared with polecats Mustela putorius - Angus Davison; Johnny D. S. Birks; Rachael C. Brookes; John E. Messenger; Huw I. Griffiths (Molecular Ecology, 2001)
The flora and fauna of Europe are linked by a common biogeographic history, most recently the Pleistocene glaciations that restricted the range of most species to southern refugial populations. Changes in population size and migration, as well as selection, have all left a signature on the genetic differentiation. Thus, three paradigms of postglacial recolonization have been described, inferred from the patterns of DNA differentiation. Yet some species, especially wide‐ranging carnivores, exhibit little population structuring between the proposed refugia, although relatively few have been studied due to the difficulty of obtaining samples. Therefore, we investigated mitochondrial variation in pine martens, Martes martes , in order to understand the extent to which they were affected by glacial cycles, and compared the results with an analysis of sequences from polecats, Mustela putorius. A general lack of ancient lineages, and a mismatch distribution that is consistent with an expanding population, is evidence that the present‐day M. martes and Mu. putorius in central and northern Europe colonized from a single European refugium following a recent glaciation. There has also been interspecific mitochondrial introgression between M. martes and the sable M. zibellina in Fennoscandia.